A novel method for ceramic characterisation by high frequency microwave energy absorption. (1st January 2021) - Kruk, Andrzej; Sorocki, Jakub; Piekarz, Ilona; Madej, Dominika; Kolenderski, Piotr
Highlights: Physicochemical characterization of the La, Nd–Y2 O3 nanosized powders and ceramics was performed. The setup to microwave energy absorption in the wide frequency range from 0.01 to 43.5 GHz was built and tested. The impact of samples' composition on the measured absorption spectral pattern was investigated and analyzed. The impact of temperature on the measured absorption spectral pattern was described. Abstract: A novel method enabling low-cost and very fast determination of physicochemical properties of solids exploring the microwave energy absorption phenomena is proposed and studied. A set of La, Nd-doped Y2 O3 ceramic samples was manufactured using the sol–gel process and free sintering. XRD analysis revealed that the crystallite size of samples is in the nanometer range A test vehicle in a form of a microstrip transmission line was tested and developed for the experiment and its shape studied enabling determination of microwave energy absorption properties of a specimen. The conducted study revealed existence of a series of narrow absorption peaks within 10 GHz−43.5 GHz correlate to the particular sample composition independent on the microstructure. The absorption peaks are shifted into lower frequency with increasing of temperature of sample. As such the proposed measurement technique was experimentally proven to be well suited for chemical composition determination.